A Study on Consumer Behaviour Towards Online Shopping in North Gujarat - Siddhapura, Akbarhusen M.; Vora, Abuzar H. (Integrated Journal for Research in Arts and Humanities, 2023)
The rising in the number of internet users in our country gives great hope for online shopping. If Internet marketers know the factors that influence customer behavior and relationships, they can create marketing strategies that change people's ability to reach loyal customers and retain existing online customers. This research paper is available on Amazon, Flipkart, myntra etc. It focuses on the consumption habits of people in the North Gujarat who do business online through e-commerce sites. As the Internet has changed the way consumers do business, many companies facing the digital revolution have changed their business services online by making purchases easy and accessible while offering customers more discounts to compete in a competitive environment like Shopping.